GliSODin® prevents airway inflammation by inhibiting T-cell differentiation and activation in a mouse model of asthma - Klein, Martin; Dijoux, Eleonore; Cheminant, Marie-Aude; Intes, Laurent; Bouchaud, Grégory (Frontiers in Allergy, 2023)
Background: Asthma is a chronic inflammatory airway disease characterized by a prevailing type 2 inflammation, airway hyperresponsiveness and mucus hypersecretion fueled by various factors among which oxidative molecules, called reactive oxygen species (ROS) play a major role. Superoxide dismutases (SODs) are enzymes that constitute the first line of defense against ROS. Melon SOD-gliadin, GliSODin®, is commonly used as a nutritional supplement with proven antioxidant properties. Objectives: In this study, we evaluated the efficacy and mode of action of two formulations of GliSODin® (melon SOD-gliadin and wheat SOD-gliadin) in the treatment of allergic asthma. Methods: House dust mites (HDM)-induced asthma mice were orally exposed to GliSODin® and airway hyperresponsiveness, lung inflammation, in vitro T cell polarization, in vivo T cell reactivation and blood immunoglobulin were investigated. Results: GliSODin® reduce airway hyperresponsiveness, lung innate and adaptive inflammation and HDM-specific IgE. CD4+ T cell coculture with HDM-sensitized dendritic cells and GliSODin® were less able to polarize in Th2 and Th17 cells. Moreover, adoptively transferred CD4+ T cells from asthmatic mice exhibit a reduced reactivation in Th2 and Th17 cells following HDM plus GliSODin® stimulation. Conclusion: GliSODin® abrogates asthma features and reduces CD4+ T cell polarization and reactivation. Altogether, these data suggest that GliSODin® could be potentially used to help for asthma symptoms management.